2021
DOI: 10.1093/nutrit/nuab096
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adaptations and effectiveness of scaled-up nutrition interventions

Abstract: Context Public health nutrition interventions shown to be effective under optimal research conditions need to be scaled up and implemented in real-world settings. Objectives The primary aim for this review was to assess the effectiveness of scaled-up public health nutrition interventions with proven efficacy, as examined in a randomized controlled trial. Secondary objectives were to: 1) determine if the effect size of scaled-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…The scaled-up evaluation could use any type of comparative design (eg RCT, quasi-RCT). Similar to previous reviews, (13)(14)(15) in order to be considered a "scaleup" the study had to be delivered on a larger scale than the original (prescale) trial, such as with a larger number of participants, and also include at least one outcome (either primary or secondary outcome) in common with the original trial to allow for comparison of effects across the trials. We supplemented this search by searching the intervention website (if available) for additional relevant publications or resources and the reference list of the published trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaled-up evaluation could use any type of comparative design (eg RCT, quasi-RCT). Similar to previous reviews, (13)(14)(15) in order to be considered a "scaleup" the study had to be delivered on a larger scale than the original (prescale) trial, such as with a larger number of participants, and also include at least one outcome (either primary or secondary outcome) in common with the original trial to allow for comparison of effects across the trials. We supplemented this search by searching the intervention website (if available) for additional relevant publications or resources and the reference list of the published trials.…”
Section: Methodsmentioning
confidence: 99%
“…A 2017 systematic review of public health interventions targeting behavioural risk factors such as smoking, alcohol, nutrition, physical activity, and obesity prevention identified just 40 scaled-up interventions globally. (12) Concerningly, reviews of obesity prevention, (13) nutrition, (14) and physical activity (15) interventions found that scaled-up interventions fail to retain their pre-scale up effect (also known as voltage drop), demonstrating less than half of their original effect. However, none of the previous reviews have included studies targeting children in the first 2 years of life.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst guidelines have the potential to underpin safe practice and provide safeguards for both patients and clinicians [47], expert and consensus approaches can go beyond high quality evidence, sometimes resulting in inappropriate recommendations [48]. However, evidence-based medicine demands 'the integration of best research evidence with clinical expertise and patient values' [49] while basing recommendations on small-scale or poorly designed trials without the application of expertise and patient values, leading to poor policy [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…However, interventions are expensive [12][13][14], and still commonly reach only a relatively small proportion of individuals [15]. Approaches and attempts to scale up interventions to promote physical activity [16] and healthy eating [17] are encouraging. Despite their success, however, existing approaches seem insufficient given the magnitude of the problem: For example, 27.5% of the world population and 81% of schoolchildren aged 11-17 are not sufficiently physically active [18], and an estimated 2 billion people worldwide are overweight or obese, largely due to an unhealthy diet [19].…”
Section: Proactive Behavior Change Techniques (Probcts) In Physical A...mentioning
confidence: 99%